A Potential Role of Interleukin 10 in COVID-19 Pathogenesis. Issue 1 (January 2021) - Lu, Ligong; Zhang, Hui; Dauphars, Danielle J.; He, You-Wen
Abstract : A unique feature of the cytokine storm in coronavirus disease 2019 (COVID-19) is the dramatic elevation of interleukin 10 (IL-10). This was thought to be a negative feedback mechanism to suppress inflammation. However, several lines of clinical evidence suggest that dramatic early proinflammatory IL-10 elevation may play a pathological role in COVID-19 severity.